Convenient approach to the synthesis of different types of schiff's bases and their metal complexes - Pradhan, Kiran; Selvaraj, Kaliaperumal; Nanda, Ashis K. (Chemistry Letters, 2010)
Various metal complexes derived from different Schiff bases are conveniently prepared using solvent-free condensation reactions in one-pot synthesis, resulting in significantly enhanced yields Initial calorimetric studies, and/or TGA of reaction mixtures, led to better optimization of reaction conditions The ligands like mines, hydrazones, semicarbazones, and nitrones are also synthesized by this method, thus this process is general and expedient